1999
DOI: 10.1143/jjap.38.1474
|View full text |Cite
|
Sign up to set email alerts
|

Collective Molecular Motion during V-Shaped Switching in a Smectic Liquid Crystal

Abstract: Abstracl. An apparatus for measurement of electro-optical Kerr effect in conductive liquids was mounted using a new pulse generator with a discrete Blumlein network and a switching system which uses an SCR b a n k instead of the usual thyratron assembly. This pulse generator is capable of producing square high voltage pulses up to 6 kV with time duration of a few microseconds and a maximum repetition rate of 100 Hz. Measurements of the Kerr constant for water, acetone and chloroform are presented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…3,4 Meanwhile, the V-shaped switching cell in which the helix is suppressed, has an average optical axis parallel to the smectic layer normal l for an applied voltage of Vϭ0. This has been confirmed by good extinction under crossed polarizers when one of them is along l. 3,5,6 Recently, Clark et al suggested the electrostatic model to explain the stabilization of molecules like this. 7 According to their model, polarization charge self-interaction becomes important with material having sufficiently large spontaneous polarization P. This makes P in the bulk align uniformly parallel to the aligning surface ( ϭ /2) through P on both surfaces heads for the surface normal ͑ ϭ0 and ͒.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…3,4 Meanwhile, the V-shaped switching cell in which the helix is suppressed, has an average optical axis parallel to the smectic layer normal l for an applied voltage of Vϭ0. This has been confirmed by good extinction under crossed polarizers when one of them is along l. 3,5,6 Recently, Clark et al suggested the electrostatic model to explain the stabilization of molecules like this. 7 According to their model, polarization charge self-interaction becomes important with material having sufficiently large spontaneous polarization P. This makes P in the bulk align uniformly parallel to the aligning surface ( ϭ /2) through P on both surfaces heads for the surface normal ͑ ϭ0 and ͒.…”
mentioning
confidence: 78%
“…[1][2][3][4][5][6][7][8] The reason for interest in them lies in their promise of realizing new types of liquid crystal displays ͑LCDs͒. 9 Since the discovery of V-shaped switching, random 1,2 and the collective models 5,6 were proposed to explain its switching mechanism. Many physical properties have been investigated which support one or both these models.…”
mentioning
confidence: 99%
“…1,3,11,13 For the preparation of an open cell, indium-tin-oxide (ITO)-coated glass was used to maintain the same conditions as a sandwiched DOI: 10.1039/b004388pcell. The glass substrate was ®rst coated with polyimide (RN1266) obtained from Nissan Chemical Industries, Ltd., and then rubbed in a single direction.…”
Section: Methodsmentioning
confidence: 99%
“…Since V-shaped switching in chiral smectic liquid crystals was reported [1] a high number of investigations have been performed to explain its origin and to analyze its electrooptical behaviour [2][3][4][5]. These materials have many advantages of ferroelectric liquid crystals (FLC) like fast response time, wide viewing angle and good contrast ratio.…”
Section: Introductionmentioning
confidence: 99%